PERANCANGAN SISTEM INFORMASI AKUNTANSI (SIA) PADA UKM A&L SHOP BENGKAYANG - B41111041, INDIRA VILIM (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
With the advancement and development of existing, currently requires all businesses accounting, including small and medium businesses. If the first time, the perception that there is only used in the accounting major companies that have a turnover and capital. However, with the increasing complexity of the financial problems faced by all actors of the business, then accounting began to be used by SMEs. This prompted the authors to conduct research on accounting information systems planning for A&L Shop Bengkayang. The method used in this research is a case study with data collection through literature study, observation, interviews, and documentation. The object of this study is a toy shop and accessories A&L Shop located at Jalan Jerendeng AR No. 53, Bengkayang, the authors of which is to assist SMEs in designing information systems accounting for SMEs can prepare its financial statements. This SMEs have implemented a simple and manual accounting record, which is done only in its expenditures and revenues are modest. Very far from the financial accounting standards, but simple bookkeeping activities have been conducted since the A&L Shop stands. The author designed the system information by using the guidelines System Development Life Cycle (SDLC) and the results of this system in the form of financial statements that are then analyzed for compliance with SAK ETAP. Keyword: accounting information system, system development life cycle (SDLC), SAK ETAP, Small and Medium-sized Entities (SMEs).